Synthesis of Biodegradable Plastics from Janeng Starch with the Addition of Chitosan as a Strengthener - Amni, Chairul; ., Ismet; Aprilia, Sri; ., Mariana (International Journal of Engineering and Technology, 2019)
Nowadays the use of plastic is very rapidly growing in the broader community. Plastics are generally used for packaging, and the purpose is to maintain the physical condition of the packaged goods and also to increase the commercial value of the goods. Most of the plastic produced have properties that are difficult to decompose so that it takes a long time for the degradation process. Over time, plastic waste has increased and caused air pollution and the environment. Plastic waste problems encourage many researchers to make plastics that are more easily degraded and safe for the environment. This type of plastic is better known as biodegradable plastic. The purpose of this study was to examine the composition of the comparison of chitosan with the addition of glycerol as a plasticizer with a concentration of 1 ml, 3 ml, 6 ml. This research produces plastic in the form of thin, transparent and elastic sheets as well as bright color, slightly yellowish. The tensile strength produced from plastics ranged from 2.3 kgf / mm2 to 4 kgf / mm2, with an elongation value of 2.1% to 4.8%, the results of the density testing contained in plastics were 2.9% to 5.1%. Microstructure measurements using SEM for bioplastic samples showed that the particles bind to each other and were quite tight so that the absorbed water was quite low.Â Â